অসমীয়া ভাষা মূকূল (প্ৰথম ভাগ) - Dutta Baruah, P.N. (Central Institute of Indian Languages Mysore, 1996)
Asamiya Bhasha Mukul (Part I) is primer for learning Assamese language, especially designed for the non-native speakers.
Asamiya Bhasha Mukul (Part I)
Keywords: Assamese; Primer; Assamese